POST-TRAUMATIC STRESS DISORDER - Yudi Artha; I Gusti Ayu Indah Ardan (Bali Journal of Medical and Health Sciences, 2013)
Post-traumatic stress disorder (PTSD) is a mental disorder that occurred after the exposure of traumatic event, which is characterized by re-experiencing, avoidance and hyperarousal. The Lifetime incidence of PTSD is estimated around 13%, and the lifetime prevalence rates ranges from 3%-78%. The exact pathophysiology of PTSD is still unclear. However, there are a number of factors that must be considered in interaction between environmental factor, personal response against stress, and psychopathology. The management of PTSD includes the use of antidepressant, CBT, and other psychotherapy. Keywords : PTSD, re-experiencing, avoidance, hyperarousal.